Quarkyonic matter and applications in neutron stars - Folias, Konstantinos; Moustakidis, Charalambos (HNPS Advances in Nuclear Physics, 2024)
We consider a quarkyonic matter model in which, for large values of density and Fermi energies, we assume particles as quasiparticles where the low Fermi momentum states are occupied by quarks and the higher states in phase space are occupied by baryons. This idea has the aim to explain with a consistent way the phase transition in the interior of a neutron star or a hybrid star and to provide an equation of state which can produce neutron stars with masses greater than 2Msun without violating causality. At extremely high density, quarkyonic matter is inferred from the properties of QCD when Nc is large and is a qualitative way to describe the particles in the momentum space. This state of matter can provide the sound velocity as a non-monotonic function of the baryon density which for higher values of density tends asymptotically to the conformal limit 1/√3.